Improving nutritive quality of palm kernel cake for poultry feeding under high environmental temperature - Mohd Ali Hanafiah, Muhamad Hakim (2021)
There has been little information on the digestibility of amino acids (AA) of treated palm kernel cake (PKC) with many inconsistencies between existing limited studies on the apparent metabolizable energy (AME) of PKC/treated PKC for broiler chickens, especially when considering high ambient temperature into account. Besides that, previous studies on the feeding of higher PKC level in poultry diet has always been incorporated with a high level of oil to compensate for the lack of available energy due to the presence of high fiber in PKC. Hence, three experiments were carried out aimed to evaluate the effects of physical and biological treatments on the nutritive quality of PKC for broiler chickens under high environmental temperature. For the first experiment, untreated PKC (UPKC), shell-less PKC (SPKC), enzyme treated PKC (EPKC), extruded PKC (XPKC), or extruded shell-less PKC (XSPKC) were fed to broilers under two environmental temperatures (24°C or 34°C for 6 h daily) to determine AME and crude protein (CP) digestibility by using difference method. EPKC had the highest AME and CP digestibility, while high ambient temperature (34°C) lower AME and CP digestibility in all PKC. In the second trial, UPKC, EPKC, extruded PKC with lower cooking temperature (XPKC-II), and lactic acid bacteria fermented PKC (LPKC) were compared for their passage rate (ROP), AME and AA digestibility in broilers under the hot and humid environmental condition. Difference method and direct method were used to determine AME and AA digestibility, respectively. LPKC had similar AME with EPKC and XPKC-II, but demonstrated highest AA digestibility. All treatments showed no effects on ROP. The study proceeds with comparing LPKC and UPKC at different oil inclusion in broiler diets. At the finisher phase, 20% of LPKC or untreated PKC were included in broiler’s diets with either 5 or 9.5% oil supplementation. LPKC and UPKC diets had no effect on broiler's growth but both diets require higher levels of dietary fat to maintain optimum growth performance. Higher level of oil supplementation in LPKC based diets reduced cecal population of E. coli and serum levels of TG, unlike the UPKC based diets. Feeding LPKC and UPKC diets at the finisher phase has not affected the nutrients digestibility, but a higher level of oil supplementation does. This was seconded by changes in the digestive enzyme activity, villus height, and mRNA expression of nutrient transporters in the higher level of oil supplemented diets fed chickens. In conclusion, LAB fermentation improved the nutritive quality of PKC for heat-stress broilers, however LPKC feeding in the finisher phase had no improvement on the growth performance but reduced gut pathogenic bacteria and blood lipid concentration. Higher oil inclusion in LPKC/UPKC diet is necessary to ensure optimum growth in chicken via improved digestive function. Such formulation/strategies could be potential for utilization of agro waste-based feed in commercial poultry production under hot and humid environmental condition.